A comparison of the severity of oral candidiasis between gestational and type 1 diabetes mellitus - Ayu Ragil Destrian Pangestu; Siti Nosya Rachmawati; Leni Rokhma Dewi; Mei Syafriadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Diabetes mellitus is a metabolic disorder caused by insufficient insulin production due to pancreatic β cell destruction, whereas in gestational diabetics an increase of hormone estrogen induces insulin resistance. Oral candidiasis constitutes an opportunistic fungal infection due to a compromised immune system that is a medical condition reported by diabetics, including those suffering from gestational diabetes. Purpose: To determine the severity of oral candidiasis in female Wistar rats with type 1 and gestational diabetes mellitus. Methods: This research constituted a laboratory experiment incorporating a post test-only group control design whose subjects were female Wistar rats divided along the following lines: group 1 consisted of diabetic non-pregnant rats, group 2 contained diabetic pregnant rats induced by streptozotocin and the control group members constituted normal female rats. Diabetes induction was performed by means of 40 mg/kgBW streptozotocin administrated intraperitoneally. Diabetes mellitus was confirmed when the blood glucose level ≥ 120 mg/dL. All groups were exposed to 0.2 ml Candida albicans suspension (5x108 CFU/ml) in the oral buccal vestibule between the distal incisors and mesial maxillary first molar for three days. A swab was performed on the third day after final exposure before the samples were observed under a light microscope. Candida albicans cultivation and calculation of the resulting colonies was carried out on Sabouraud Dextrose Agar after they had been identified by means of a germ tube test. Results: The result confirmed the absence of hyphae in the control group, while in group 1 all samples contained hyphae. Moreover, group 2 featured a dense hyphae population. A chi-square test indicated a statistical significance (p<0.05) between all groups. Conclusion: Oral candidiasis in gestational diabetes is more severe than that occurring during type 1 diabetes mellitus.